Juan Valdano: hablará por sí mismo siempre (In Memoriam: Cuatro autores en tiempo presente; Humberto E. Robles, Juan Valdano, Eliécer Cárdenas Espinosa y Jorge Velasco Mackenzie. Testimonios, legados y relecturas) - Ponce Maldonado, Modesto (2022)
This text remembers and exalts the man, and at the same time the multifaceted writer and university professor Juan Valdano, who cultivated essays, research, novels and short stories. It evokes the Ecuadorian who celebrated the country by dedicating more than one work to our way of being, to our idiosyncrasy, to our sense of nationhood. He studied Philosophy and Literature in Cuenca, Hispanic Philology in Madrid and French Literature in Provence. Member of the Ecuadorian Academy of Language, he received several awards and distinctions such as the Eugenio Espejo Award for his career and his works. As a tribute to his memory, a critical commentary is added to a personal anthology of his short stories entitled Juegos de Proteo (2012).